Two Novel Bacteriophages Control Multidrug- and Methicillin-Resistant Staphylococcus pseudintermedius Biofilm - Kim, Sang Guen; Giri, Sib Sankar; Yun, Saekil; Kim, Sang Wha; Han, Se Jin; Kwon, Jun; Oh, Woo Teak; Lee, Sung Bin; Park, Yong Ho; Park, Se Chang (Frontiers in Medicine, 2021)
As a primary bacterial pathogen in companion animals, Staphylococcus pseudintermedius has zoonotic potential. This pathogen exhibits multidrug resistance, including resistance to methicillin, and biofilm-forming ability, making it hard to eradicate with antimicrobial agents. One potential alternative is bacteriophage therapy. In this study, we first characterized the antimicrobial resistance profile of S. pseudintermedius from canine samples and isolated two novel bacteriophages, pSp-J and pSp-S, from canine pet parks in South Korea to potentially control S. pseudintermedius. The biological characteristics of phages were assessed, and the phages could infect most of the methicillin-resistant S. pseudintermedius strains. We found that these phages were stable under the typical environment of the body (~37 °C, pH 7). We also assessed bacterial lysis kinetics using the two phages and their cocktail, and found that the phages could prevent biofilm formation at low doses and could degrade biofilm at high doses. Taken together, this study demonstrates that bacteriophages pSp-J and pSp-S isolated in this study can be used to potentially treat methicillin-resistant S. pseudintermedius.